2021
DOI: 10.1101/2021.07.15.21260572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Financial burden of Chronic Kidney Disease Patients on Maintenance Hemodialysis in Chittagong, Bangladesh

Abstract: Background: Chronic kidney disease (CKD) is an important public health problem. Renal replacement therapy (RRT) is needed to patients who goes to end stage renal disease(ESRD). Most of the evidence on its costs relates to patients receiving dialysis or kidney trans-plants, which shows that, in these phases, CKD poses a high burden to payers. The aim of this study was to estimate the financial burden of patients with CKD on maintenance hemodialysis. Methods: It is one -year observational study, carried out to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is also the case for uninsured patients or resource-poor; such patients present with later stages of CKD when hospitalized primarily due to barriers to receiving timely or preventative care. [20][21][22] This is exacerbated by the lack of pediatric nephrologists in speci c geographic regions. Kula and Somers demonstrated that a lack of pediatric nephrologists in some states can have a myriad of problems ranging from lack of access to care to reduced surveillance of CKD, decreasing the reported true incidence and prevalence of pediatric CKD.…”
Section: Indiamentioning
confidence: 99%
“…This is also the case for uninsured patients or resource-poor; such patients present with later stages of CKD when hospitalized primarily due to barriers to receiving timely or preventative care. [20][21][22] This is exacerbated by the lack of pediatric nephrologists in speci c geographic regions. Kula and Somers demonstrated that a lack of pediatric nephrologists in some states can have a myriad of problems ranging from lack of access to care to reduced surveillance of CKD, decreasing the reported true incidence and prevalence of pediatric CKD.…”
Section: Indiamentioning
confidence: 99%